Polo-like kinase-1, Aurora kinase A and WEE1 kinase are promising druggable targets in CML cells displaying BCR::ABL1-independent resistance to tyrosine kinase inhibitors - Mancini, Manuela; De Santis, Sara; Monaldi, Cecilia; Castagnetti, Fausto; Lonetti, Annalisa; Bruno, Samantha; Dan, Elisa; Sinigaglia, Barbara; Rosti, Gianantonio; Cavo, Michele; Gugliotta, Gabriele; Soverini, Simona (Frontiers in Oncology, 2022)
In chronic myeloid leukemia (CML), Aurora kinase A and Polo like kinase 1 (PLK1), two serine-threonine kinases involved in the maintenance of genomic stability by preserving a functional G2/M checkpoint, have been implicated in BCR::ABL1-independent resistance to the tyrosine kinase inhibitor (TKI) imatinib mesylate and in leukemic stem cell (LSC) persistence. It can be speculated that the observed deregulated activity of Aurora A and Plk1 enhances DNA damage, promoting the occurrence of additional genomic alterations contributing to TKI resistance and ultimately driving progression from chronic phase to blast crisis (BC). In this study, we propose a new therapeutic strategy based on the combination of Aurora kinase A or PLK1 inhibition with danusertib or volasertib, respectively, and WEE1 inhibition with AZD1775. Danusertib and volasertib used as single drugs induced apoptosis and G2/M-phase arrest, associated with accumulation of phospho-WEE1. Subsequent addition of the WEE1 inhibitor AZD1775 in combination significantly enhanced the induction of apoptotic cell death in TKI-sensitive and -resistant cell lines as compared to both danusertib and volasertib alone and to the simultaneous combination. This schedule indeed induced a significant increase of the DNA double-strand break marker γH2AX, forcing the cells through successive replication cycles ultimately resulting in apoptosis. Finally, combination of danusertib or volasertib+AZD1775 significantly reduced the clonogenic potential of CD34+ CML progenitors from BC patients. Our results may have implications for the development of innovative therapeutic approaches aimed to improve the outcomes of patients with multi-TKI-resistant or BC CML.